The Impact of Technology, Job Complexity and Religious Orientation on Managerial Performance - Jesmin Islam; Majharul Talukder; Hui Hu (Australasian Accounting, Business and Finance Journal, 2012)
This paper explores the impact of technology, job complexity and religious orientation on the performance of managers in the financial services industries. Data were collected from bank managers representing Islamic and conventional banks in Bangladesh. Path models were used to analyse the data. The results provide support for the hypothesis that a management accounting systems (MAS) adequacy gap exists in the financial sector in a developing country such as Bangladesh. These Islamic and conventional banks also experienced varied outcomes regarding the impact of the MAS adequacy gap on managerial effectiveness. Significant results emerged concerning the direct influence of technology and job complexity on managerial effectiveness, although these findings again differed across religious and conventional banks. Significant intervening effects of both MAS adequacy gap and job complexity on the relationships between contingency factors and managers' effectiveness were also found. Overall the findings showed that the type of religious orientation in Islamic banks wielded an important influence on the sensitivity of the MAS adequacy gap. Religious orientation served as a control device for the relationships between job-related contingency factors and managerial effectiveness.
Keywords: Management accounting systems; technological advancement; job complexity; religious orientation; managerial effectiveness.